A Potential Target for Diabetic Vascular Damage: High Glucose-Induced Monocyte Extracellular Vesicles Impair Endothelial Cells by Delivering miR-142-5p - Zhang, Rui; Niu, Shuai; Rong, Zhihua; Li, Fengshi; Ni, Leng; Di, Xiao; Liu, Changwei (Frontiers in Bioengineering and Biotechnology, 2022)
Endothelial dysfunction is a key accessory to diabetic cardiovascular complications, and the regulatory role of the extracellular vesicles (EVs) from the innate immune system is growing. We tested whether EVs derived from high glucose-induced monocytes could shuttle microRNAs and impair endothelial cells. EVs from high glucose- and basal glucose-treated THP-1 cells (HG-THP-1 EVs and BG-THP-1 EVs) were isolated and identified. After coculture with THP-1 EVs, human umbilical vein endothelial cells (HUVECs) were tested by proliferation, migration, reactive oxygen species (ROS) detection assays, and western blot for Nrf2/NLRP3 signaling. MiR-142-5p was predicted by miRNAs databases and further verified by RT–qPCR and dual-luciferase reporter gene assays that inhibit Nrf2 expression. The regulation of miR-142-5p in HUVECs was further evaluated. A type 1 diabetes mellitus (T1DM) mouse model was developed for miR-142-5p inhibition. Aorta tissue was harvested for hematoxylin-eosin staining and immunohistochemistry of interleukin-1β (IL-1β). Compared to BG-THP-1 EVs, HG-THP-1 EVs significantly reduced migration and increased ROS production in HUVECs but did not affect proliferation. HG-THP-1 EVs induced suppression of Nrf2 signaling and NLRP3 signaling activation. RT–qPCR results showed that HG-THP-1 EVs overexpressed miR-142-5p in HUVECs. The transfection of miR-142-5p mimics into HUVECs exhibited consistent regulatory effects on HG-THP-1 EVs, whereas miR-142-5p inhibitors demonstrated protective effects. The miR-142-5p antagomir significantly reduced the IL-1β level in T1DM aortas despite morphological changes. To conclude, miR-142-5p transferred by high glucose-induced monocyte EVs participates in diabetic endothelial damage. The inhibition of miR-142-5p could be a potential adjuvant to diabetic cardiovascular protection.